Compound Word in Harry Potter’s Novel “The Goblet of Fire” - Dewi, Putu Feby Chintya; Sedeng, I Nyoman; Indriani, Ketut Santi (Humanis, 2020)
This study is aimed at analyzing types and meanings of the compound words in Harry Potter’s: Goblet of Fire. The data were taken using documentation method and note-taking technique. Qualitative method was applied to analyze the data. The theory that was used in identifying the types of compound words is the theory of compound proposed by Lieber (2009). The results showed that there are three types of compound words found in the Harry Potter’s Novel, they are; attributive compound, coordinative compound, and subordinative compound.  Based on the second problem, about the analysis of meaning, most of compound words has the general meaning or meaning just like in the dictionary, on the other hand a few compound words are constructed differently in Harry Potter’s novel.